2023
DOI: 10.1007/s44202-023-00068-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depression among women in Afghanistan: a cross-sectional study

Abstract: Depression is a very common mental health illness characterized by a cluster of signs and symptoms ranging from mood disturbances and sleep or appetite disorders to physical manifestations of the body. The purpose of the present study was to estimate the prevalence of depression and its related factors among Afghan women. A cross-sectional study was conducted among women between July 14, 2021, to August 15, 2021, in Kabul, Mazar-e-Sharif and Samangan provinces (Afghanistan). A total of 664 Afghan women partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
4
10
0
1
Order By: Relevance
“…Almost three-quarters of participants reported anxiety symptoms (71.9%) with those aged over 34 years reporting a higher prevalence (84.9%), in contrast to those aged under 35 years (66.7%). This is in line with ndings of a previous study among women in Afghanistan (n = 438) which reported that the prevalence of anxiety among older participants (75.6%) was higher than younger ones (89.1%) [23], a nding that is generally supported in the literature [22][23]. This differs from ndings in a study conducted in Iran (n = 7886), where the prevalence of anxiety was reported to be higher among younger participants (20.1%) than older participants (13.8%) [35].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Almost three-quarters of participants reported anxiety symptoms (71.9%) with those aged over 34 years reporting a higher prevalence (84.9%), in contrast to those aged under 35 years (66.7%). This is in line with ndings of a previous study among women in Afghanistan (n = 438) which reported that the prevalence of anxiety among older participants (75.6%) was higher than younger ones (89.1%) [23], a nding that is generally supported in the literature [22][23]. This differs from ndings in a study conducted in Iran (n = 7886), where the prevalence of anxiety was reported to be higher among younger participants (20.1%) than older participants (13.8%) [35].…”
Section: Discussionsupporting
confidence: 92%
“…More speci cally, those with a low family monthly income recorded a higher prevalence of anxiety (75.7%) in comparison to those with a high family monthly income (47.3%). This nding is in line with the ndings of a previous study in Afghanistan (n = 664) that reported higher prevalence of anxiety among low monthly family income participants compared to high income monthly family income [22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations